Diseño e implementación de un transductor electrónico para la medición de flujo a canal abierto en los afluentes de la microcuenca del río El Pisque en el cantón Cayambe - Guerra Machado, María Eugenia (2016)
In Borja Toma there is a community system for distribution of water to pasture, so the need to build an electronic transducer that measures the flow to verify this irrigation system in open channel, for which several methods are investigated and their characteristics, the method of Section and Speed is selected. The simulation of the operating principle is made, and then a modeling in Matlab software, which served to understand the mathematical treatment of the variables, the reel to be used has 16 blades to capture the constant movement of water. The treatment of variables: speed, height and base of channel is performed in an Arduino UNO card, and the flow rate in liters per second is watching in an LCD display, which values are stored on a memory card so that then operator system can remove it and download the information into a computer for analysis. The system is powered by a 12 V battery and it is connected to a solar panel, to ensure prolonged operation of the transducer. Once installed transducer were made performance tests with satisfactory results, achieved measuring the flow of water in one of the channels of the creek of the left side of microwatershed of El Pisque River.